2020
DOI: 10.1093/ndt/gfz277
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function and symptom development over time in elderly patients with advanced chronic kidney disease: results of the EQUAL cohort study

Abstract: Background Initiation of renal replacement therapy often results from a combination of kidney function deterioration and symptoms related to chronic kidney disease (CKD) progression. We investigated the association between kidney function decline and symptom development in patients with advanced CKD. Methods In the European Quality study on treatment in advanced CKD (EQUAL study), a European prospective cohort study, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…43,44 Several studies report that the symptom burden in CKD is high. 1,45 In other publications from the EQUAL cohort, we have observed that the number and burden of symptoms increase progressively as renal function deteriorate. 45 Moreover, a higher symptom burden has also been associated to a lower quality of life.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…43,44 Several studies report that the symptom burden in CKD is high. 1,45 In other publications from the EQUAL cohort, we have observed that the number and burden of symptoms increase progressively as renal function deteriorate. 45 Moreover, a higher symptom burden has also been associated to a lower quality of life.…”
Section: Discussionmentioning
confidence: 79%
“…1,45 In other publications from the EQUAL cohort, we have observed that the number and burden of symptoms increase progressively as renal function deteriorate. 45 Moreover, a higher symptom burden has also been associated to a lower quality of life. 2 In our present study, we found that both constipation and decreased appetite were risk factors for decline in nutritional status.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, Dawson et al found an association between taste disturbances and constipation prevalence [ 37 ], while the EQUAL study showed that constipation was an independent predictor of a decline in nutritional status [ 23 ]. Finally, Murtagh et al showed that the prevalence of constipation within a month before death was 1.87 times higher than in the whole baseline CKD group [ 62 , 63 ]; nonetheless, the increase in the prevalence of constipation in CKD patients was evidenced also over the 1-year follow-up period in the EQUAL study [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated a faster kidney decline in men compared with women in the EQUAL population 12 , and others have demonstrated that lower levels of eGFR correlate well with lower HRQOL 39 . In addition, a faster decline in kidney function is associated with a steeper increase in symptom burden 41 , which in turn negatively affects HRQOL.…”
Section: Discussionmentioning
confidence: 99%